Pola Cluster Geospatial Eksplorasi Kejahatan Narkoba di DKI Jakarta - Raymond Sunardi Oetama; Tan Thing Heng; David Tjahjana (ULTIMA InfoSys, 2020)
This study is focused on building some visualizations of crimes that occur in the Jakarta area in general, and specifically on drug problems. As the largest city in Indonesia, Jakarta faces the highest number of crimes throughout Indonesia. But unfortunately, there is a lack of geospatial visualization about crime in Jakarta. The visualizations are presented as some cluster models. These models show which parts of Jakarta with a high level of crime, the biggest crimes in Jakarta, and the types of crimes that occur in Jakarta. The biggest crime in Jakarta is also explained with some additional information such as the type of crime, age, and distribution. Clustering is divided into three, which are high, medium, and low. The grouping model was built using Tableau with the K-means algorithm. The results of this study can be used for the Provincial Government of DKI Jakarta to make strategic plans to develop actions that can reduce crime rates in Jakarta.